IFA and PIFA Size Reduction by Using a Stub Loading - Jose Alfredo Tirado-Mendez; Rene Acevo-Herrera; Ruben Flores-Leal; Roberto Linares-Miranda; Hildeberto Jardon-Aguilar (International Journal of Antennas and Propagation)
A proposed technique for size reduction of a conventional inverted-F antenna (IFA) and a planar inverted-F antenna (PIFA) by employing a reactive load generated by a short-circuited stub is presented. The reduction factor of both antennas is around 30%, and the main parameters of the devices are preserved, including a fractional bandwidth of 4% and a gain of −2 dB. Both antennas operate around 1.5 GHz.